Site-Specific Traffic Loading Estimation Challenges in Structural Pavement Design Process in Qatar: A Case Study - Al-Tawalbeh, Ahmad; Sadeq, Mohammed; Sadek, Husam (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Upon the design of any pavement structure, three fundamental external design parameters have to be considered throughout the design process: the characteristics of the subgrade, traffic loads, and environmental conditions. This paper focuses on the main challenges being faced to estimate site-specific traffic loading for a pavement design due to the lack of accurate and recent traffic data. A case study for a pavement structural design process for an actual expressway project in the State of Qatar is discussed in this paper. This case study goes through traffic loading calculations inputs; the Average Daily Traffic (ADT), Truck Factor (TF), as well as Heavy Good Vehicle Percentage (HGV%). The challenges of calculating these site-specific traffic loading inputs are discussed through investigation of the accuracy in traffic loading estimation using Qatar Strategic Transport Model (QSTM), and how the model can be incorporated in the design. Besides, limited available Wight-In-Motion (WIM) surveys have been discussed and the paper ends with the conclusion that rich availability of traffic data enhances the accuracy of the pavement structural design. It affects significantly the value engineering practice, and results in sustainable pavement sections.